2023
DOI: 10.1073/pnas.2303224120
|View full text |Cite
|
Sign up to set email alerts
|

Fully accessible fitness landscape of oncogene-negative lung adenocarcinoma

Maryam Yousefi,
Laura Andrejka,
Márton Szamecz
et al.

Abstract: Cancer genomes are almost invariably complex with genomic alterations cooperating during each step of carcinogenesis. In cancers that lack a single dominant oncogene mutation, cooperation between the inactivation of multiple tumor suppressor genes can drive tumor initiation and growth. Here, we shed light on how the sequential acquisition of genomic alterations generates oncogene-negative lung tumors. We couple tumor barcoding with combinatorial and multiplexed somatic genome editing to characterize the fitnes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…We also assessed the number of clonal barcoded tumors in each mouse and found that H11 LSL-Cas12a mice had an average of 2-fold more tumors than Kras LSL-G12D mice when corrected for viral titer ( Figure 3c ). These results are consistent with the high tumorigenic potential of lung epithelial cells with combined inactivation of Nf1 , Rasa1 , and Pten 19,23 , as well as efficient multiplexed genome editing by Cas12a. Tumor sizes in H11 LSL-Cas12a mice were dramatically larger than in KT mice, with the log-normal mean tumor size around 4-fold greater in H11 LSL-Cas12a mice ( Figure 3d ), in line with an increased tumor growth rate for cr Nf1/Rasa1/Pten tumors compared to those driven by oncogenic KRAS.…”
Section: Resultssupporting
confidence: 85%
“…We also assessed the number of clonal barcoded tumors in each mouse and found that H11 LSL-Cas12a mice had an average of 2-fold more tumors than Kras LSL-G12D mice when corrected for viral titer ( Figure 3c ). These results are consistent with the high tumorigenic potential of lung epithelial cells with combined inactivation of Nf1 , Rasa1 , and Pten 19,23 , as well as efficient multiplexed genome editing by Cas12a. Tumor sizes in H11 LSL-Cas12a mice were dramatically larger than in KT mice, with the log-normal mean tumor size around 4-fold greater in H11 LSL-Cas12a mice ( Figure 3d ), in line with an increased tumor growth rate for cr Nf1/Rasa1/Pten tumors compared to those driven by oncogenic KRAS.…”
Section: Resultssupporting
confidence: 85%
“…As a result, they may have relatively little room to increase their proliferation even further compared to tumors without such a strong oncogenic driver. Concordantly, we previously showed that the combined inactivation of Nf1, Rasa1 and Pten was highly synergistic in oncogene-negative lung adenocarcinoma 39,40 .…”
Section: Discussionsupporting
confidence: 70%
“…Conversely, while barcoded dual-sgRNA vectors have led to key insights into the tumorigenic potential of complex tumor genotypes in vivo, they have required laborious individual cloning [39][40][41][42] and/or have suffered from lentiviral template switching that decouples the barcode from the sgRNA 43 . To generate barcoded lentiviral-sgRNA vector pools for tumor barcoding and highthroughput barcode sequencing (Tuba-seq), we recently integrated a diverse barcode within the 21 nucleotides of the U6 promoter directly adjacent to a single sgRNA (U6 barcode Labeling with per-Tumor Resolution Analysis; Tuba-seq Ultra ) 44 .…”
Section: Generation Of Barcoded Lentiviral Libraries For Dual Sgrna S...mentioning
confidence: 99%